"I Understand the Struggle": Leveraging the Lived Experiences of African American Teachers in TESOL. Issue 4 (6th February 2015) - Siefert, Bobbi; Salas, Spencer; D'amico, Mark m.
Abstract : Although TESOL in‐service teacher education committed to culturally sustaining pedagogy (Paris, 2012) has underscored the critical role of teachers' professional subjectivities for student achievement, relatively few studies have attempted to capture the perspectives of African American classroom teachers working with English language learners in U.S. contexts. The authors bring qualitative data from a participatory study to argue that the vivencias of Ellie Washington, an African American first‐grade teacher born and raised in the segregated southern United States, was the lens through which she understood the TESOL in‐service development in which she had participated 5 years earlier, her advocacy for Latino transnationals, and her hesitations about the exclusivity of ESL programming. Extending contemporary conversations about teacher quality in the "aftermath of scripted curriculum policies" (Maniates & Mahiri, 2011, p. 10), this article centers on how Washington's lived experiences shaped her interactions with Latino immigrant schoolchildren in rural North Carolina. The authors argue that, in spite of a needed emphasis on developing classroom teachers' sociocultural competencies for working with children of immigration, too often there is an erasure of the lived experiences of teachers of color and the funds of knowledge (Moll, 2014) those experiences potentially represent for highly qualified teaching.